The Influence of The Lecture Method on The Learning Nahwu at PBA Students Of INKAFA Gresik - Farid Qomaruddin (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Lectures are methods that can be applied in teaching, that is, how to carry out teaching by conveying information and knowledge to students. Student interest in learning in the Nahwu course is a sense of interest in the course without coercion from outside parties, resulting in changes in individual behavior. This study aimed to determine the influence of the lecture method on Nahwu's learning interest in PBA students in the second semester at Inkafa Gresik. This research method is a pre-experiment that uses a quantitative approach. The population of the researchers made respondents amounted 22 students. Tests and questionnaires were used for the data collection. The data analysis used the Likert scale formula and Product Moment. The results of the data analysis show that the application category of the lecture method is